"Financialization" of public discourse: The case of AIG. Issue 4 (23rd August 2014) - Avsar, Rojhat Berdan
Abstract : Purpose: The paper intends to demonstrate a particular shift in the language used in economic policy debates since the late 70s. We call this phenomenon "financialization of public discourse" which refers to the use of particular metaphors and linguistic styles that are friendly to the economic interest of the financial industry. Design/methodology/approach: We used a rhetorical analysis to discover and analyze the specific cases which exemplify what we call financialization of public discourse. A case study, the U.S. Treasury's justification for its AIG policy, is utilized to strengthen the thesis of the paper. Findings: There is convincing evidence that the financialization of public discourse is pervasive. As the AIG case helps demonstrate, the language of finance limits the policy conversation and disguises the fact that the government's role in this case is not different that its overall collective risk management function. Research limitations/implications: We assume that framing of economic events helps shape public perceptions about the desirability of various policies. This prediction, although reasonable, should be supported with more direct evidence. Practical implications: This paper intends to articulate a vital risk management role that the government plays in the economy. Specifically, the government is strongly suited to spreading the consequences of aggregate risk over time and thereby insulating the individuals from drastic fluctuations in their welfare. This approach could potentially inform an array of public policies. Originality/value: The rhetorical strategies that policy makers use to justify their policy positions and their consequences have been certainly under-researched, particularly in economics. This paper intends to fill this gap in the literature.